In vivo degradation rate of alginate–chitosan hydrogels influences tissue repair following physeal injury. Issue 6 (8th February 2020) - Erickson, Christopher B.; Newsom, Jake P.; Fletcher, Nathan A.; Feuer, Zachary M.; Yu, Yangyi; Rodriguez‐Fontan, Francisco; Hadley Miller, Nancy; Krebs, Melissa D.; Payne, Karin A.
Abstract: The physis is a cartilaginous tissue in children's long bones that is responsible for bone elongation. Physeal injuries can heal with bony repair tissue known as a "bony bar, " and this can cause growth deformities. Current treatments involve surgical resection of the bony bar and insertion of inert materials in hopes of preventing bony bar re‐formation and preserving bone elongation. However, these materials frequently fail and the bony bar commonly returns. This study investigated alginate–chitosan hydrogels as interpositional materials to block bony bar formation in a rat model of physeal injury. Further, biomaterial properties such as substrate stiffness, permeability, and degradation rate were studied. Different ratio alginate:chitosan hydrogels with or without calcium cross‐linking were tested for their inhibition of bony bar formation and restoration of the injured physis. Alginate:chitosan were mixed (a) 90:10 with calcium (90:10 + Ca); (b) 50:50 with calcium (50:50 + Ca); (c) 50:50 without calcium (50:50 − Ca); and (d) 50:50 made with irradiated alginate (IA) and without calcium. We found that repair tissue was determined primarily by the in vivo degradation rate of alginate–chitosan hydrogels. 90:10 + Ca had a slow degradation rate, prevented cellular infiltration, and produced the most bony bar tissue while having softer, more permeable material properties. IA had the fastest degradation, showed high cellular infiltration, and produced the most cartilage‐like tissue while having stiffer, less permeable material properties. Our results suggest that the in vivo biomaterial degradation rate is a dynamic property that can be optimized to influence cell fate and tissue repair in physeal injuries.